2001
DOI: 10.1359/jbmr.2001.16.5.925
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Added to Established Hormone Therapy: Effects on Vertebral Fracture and Maintenance of Bone Mass After Parathyroid Hormone Withdrawal

Abstract: Our best pharmacologic agents for osteoporosis treatment prevent no more than 40 -60% of osteoporotic fractures in patients at highest risk. Thus, there is a need for agents that can further augment bone mass and reduce fracture risk more substantially. To this end, we investigated the utility of parathyroid hormone (PTH) in combination with established hormone-replacement therapy (HRT) in women with osteoporosis. Fifty-two women who had been on HRT for at least 2 years were enrolled in this trial in which 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
169
0
17

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(193 citation statements)
references
References 27 publications
5
169
0
17
Order By: Relevance
“…124 Estrogen and raloxifene do not appear to have the blunting effect on PTH therapy. [125][126][127][128] Fracture data are lacking and combination therapies are usually not recommended. Sequential therapies preceding or following PTH treatment are useful in maintaining and enhancing bone mass.…”
Section: Combination Therapymentioning
confidence: 99%
“…124 Estrogen and raloxifene do not appear to have the blunting effect on PTH therapy. [125][126][127][128] Fracture data are lacking and combination therapies are usually not recommended. Sequential therapies preceding or following PTH treatment are useful in maintaining and enhancing bone mass.…”
Section: Combination Therapymentioning
confidence: 99%
“…Prior studies evaluating combinations of PTH or teriparatide with antiresorptive agents have yielded inconsistent results, with differences related to which antiresorptive agent is used, (16)(17)(18)(19)(20)(21)(22) whether patients are treatment-naive or have been on antiresorptive therapy when combination treatment is started, (14,23) and, for patients on prior antiresorptives, whether the antiresorptive agent is continued or stopped when teriparatide is added. (24) In one study, (14) treatment-naive patients were randomized to alendronate or intact PTH(1-84) monotherapy versus combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3)(4) In contrast to conventional antiresorptive agents, which reduce bone resorption and ultimately suppress bone formation, (5)(6)(7) PTH stimulates bone formation. (1)(2)(3)(4)(8)(9)(10) In humans, bone formation markers, including bone-specific alkaline phosphatase (BSALP) and osteocalcin, are increased within a month of initiation of daily injection of hPTH , whereas PTH-induced increases in resorption markers catch up about 6 months later. (1)(2)(3)8) In addition, histomorphometric analysis of human iliac crest bone biopsies using quadruple tetracycline labeling revealed that daily injection of hPTH(1-34) (25 g/day) directly stimulated bone formation without any significant increase in bone resorption within 6 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3)(4)(8)(9)(10) In humans, bone formation markers, including bone-specific alkaline phosphatase (BSALP) and osteocalcin, are increased within a month of initiation of daily injection of hPTH , whereas PTH-induced increases in resorption markers catch up about 6 months later. (1)(2)(3)8) In addition, histomorphometric analysis of human iliac crest bone biopsies using quadruple tetracycline labeling revealed that daily injection of hPTH(1-34) (25 g/day) directly stimulated bone formation without any significant increase in bone resorption within 6 weeks. (8) These findings suggest that daily PTH injection induces bone formation without prior resorption on initiation of therapy.…”
Section: Introductionmentioning
confidence: 99%